Team roles at work - Belbin, R. Meredith; Brown, Victoria (Routledge, Taylor & Francis Group, 2023)
Considered one of the first and most important 'management gurus', the name Belbin is synonymous with Team Role theory, a familiar concept for managers and management trainers across the world. This fully updated third edition of Team Roles at Work provides the practical application of the theory in everyday work situations. This new edition has up-to-date practical examples and summaries to reflect contemporary scenarios, and a brand-new chapter on remote team working, an issue that has gained even greater significance in recent times. The book also includes a Foreword to capture the impact of Meredith's work in the field of management and team working. Further information accompanies the book on the Belbin website, www.belbin.com, including a summary of the nine Team Roles with their icons, descriptions, strengths and allowable weaknesses. Team Roles at Work is the best-selling, second book written by Meredith Belbin, designed for any manager who wants to understand the practical application of Team Role theory"--